(3OjhGf GHf ecGfSs - (3GHf ecGfS , YHO GdQMef Hf YHO GdQRGb Hf EHQGgje, aNQ GdOjf CHh GdaQL,J (B794 (3g` s ((3aVd Gddg Hf CHj GdaQL YHOGdQMef Hf ecGfS s)
(3ChdgG (B:s
(3bGd(B: (3jUa SQMI Ydi TGWF Gdfjd(B: (3jGSQMI GdTGWF GdefSGH chKQg Ydi GdjhGbjJ aj CTcGd MUHGA s
(3BNQgG (B:s
(3hGddg eSFhd dfG GdgOGjI aj eHOC Gdbhd dg GdfgGjI GfJgJ Ydi jO cGJHgG hdO GdeUfa jdjgG CQLhRI YedgG hSeGgG YeOI GdMQaG s
(3fSNI KGfjI s
(3hQO CjVG JMJ Qbe (B481 (3, (B848 (3, (B2180s
(3jfbUgG GdebOeIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs